在中國思考“本體”：以熊十力、張東蓀的對話爲線索: Thinking “Substance” in China: A Dialogue between Xiong Shili and Chang Tung-sun as a Clue - 蔡岳璋 (人文中國學報, 2023)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 上個世紀三〇年代，中國哲學家張東蓀討論中國是否關心萬物背後有無本質（ultimatestuff）的問題時曾經指出：中國思想上，自始即無所謂“本體”（substance）的觀念，這樣的現象反映在早期漢語上，即查無此一概念之詞。這樣的主張，適與同時代力倡“體用論”的熊十力，形成强烈對比。本文以晚清民初中西文化斡旋之際，現代中國哲學界的兩枝棟梁爲根據，透過熊十力、張東蓀的往復争辯及各自哲學判斷的差距爲線索，試圖挖掘傳統世界觀在現代知識語言更新的轉譯時期，所激蕩起的豐富的文化體會、理解與想象，顯豁本體之説的合法限度與正當性依據。 In the 1930s, the Chinese philosopher Chang Tungsun (1886-1973), in discussing whether China pays attention to the issue of whether there is ultimately substance in all things, pointed out that the concept of “substance” had never existed in China since the beginning. Such a phenomenon is reflected in the archaic Chinese language, which includes no such word representing this notion. This statement sharply contrasts with Xiong Shili’s (1885-1968) emphasis on “Substance-function Theory” (tiyong lun 體用論) advocated in the same era. This essay takes these two eminent figures of the late Qing Dynasty and modern Chinese philosophy as its subject of investigation. Through the correspondence between Xiong Shili and Chang Tung-sun and the discrepancy between their respective philosophical judgments, it attempts to uncover the rich cultural understanding, comprehension, and imagination that traditional worldviews have stirred up in modern times, and to further explain the legitimate limits and proper bases of ontological discourses.